Analysis of gut microbiota-derived metabolites regulating pituitary neuroendocrine tumors through network pharmacology - Cao, Min; Huang, Ping; Xu, Lun-shan; Zhang, Yi-hua (Frontiers in Pharmacology, 2024)
Pituitary neuroendocrine tumors (PitNETs) was a special tumor of central nervous system, which was closely related to metabolism, endocrine and immunity. Network pharmacology was used to determine the metabolites and pharmacological mechanism of gut microbiota regulating PitNETs. The metabolites of gut microbiota were obtained from gutMGene database, and the targets related to metabolites and PitNETs were determined via public database. A total of 208 metabolites were mined in gutMGene database, 1192 metabolite targets were screened from Similarity Ensemble Approach (SEA) database, and 2303 PitNETs-related targets were screened from GeneCards database. A total of 392 overlapping targets of metabolites targets and PitNETs-related targets were screened out. Finally, the intersection targets of the overlapping targets and gutMGene database targets (223 targets) were screened as core targets (43 targets).Combined with Kyoto Encyclopedia of Genes and Genomes (KEGG) signaling pathway and metabolic pathway analysis, CXCL8 was screened as a hub target, tryptophan metabolism was screened as a key metabolic pathway, IL-17 signaling pathway was screened as the key KEGG signaling pathway. In addition, molecular docking analysis of active metabolites and target were carried out，the results revealed that baicalin, baicalein and Compound K have good binding activity with CXCL8. In this study, we described the potential mechanism for treating PitNETs from the microbiota (Bifidobacterium adolescentis), signaling pathway (IL-17 signaling pathway), target (CXCL8), metabolites (baicalin, baicalein and Compound K), which provided scientific basis for further study.